Penerapan alat pengepres ampas tahu untuk pengrajintempe gembus pada sentra industri tahu `Ngudi Lestari',Srandakan, Bantul - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Soybean, as a protein source to human being, is widely processed to become tofu. During the process, together with tofu, solid and liquid waste are also produced in a considerable amount. Even, it is considered that tofu waste have a great prospect to be developed further either as a raw material or as supporting one containing a nutritive value, their utilization is not yet widely conducted. Major constrains faced by the most industries is that the separation of liquid in the waste is still traditionally done using stone over a wooden block. It seems that these process does not produce a proper yield since it still has a high moisture content. Due to this condition, a new appropriately technological and an easy to operate equipment should be introduced. A study on this newly urgent tofu waste pressing equipment composes of designing constructing, fabricating of the proposed equipment. Testing and evaluating will be focused on the technological appropriateness, ergonomic, operation requirements. economy and acceptability to the small scale industries Field test upon the proposed equipment showed that there is a significantly reduction of the processing time of about 300 - 400% compared to the that of traditional one. The waste of 63 kg needs only 60 minutes reacting a moisture content reduction of 8 to 10% wet basis, while 180 - 240 minutes is taken at the same amount of waste weight by traditional equipment. The above result shows that there is an increasing efficiency and productivity with relatively law production cost since this equipment is built from materials (wood, Iron and steel) available in local market.